Rare Case: Enteric Type Lung Adenocarcinoma with Exon 21 Mutation Mimicking Thymic Adenocarcinoma: Rare Case: Enteric Type Lung Adenocarcinoma with Exon 21 Mutation Mimicking Thymic Adenocarcinoma - Adolf Nggay, Andriana; Dwi Pratiwi, Suryanti; Jane Sugiri, Yani; Rachma Erawati, Dini; Setyo Yudhanto, Hendy; Elisabeth, Gracelia (Universitaas Brawijaya, 2026)
Background: Enteric type lung adenocarcinoma is a very rare variant of pulmonary adenocarcinoma, with a prevalence of about less than 1% of all cases(2). Due to the similarity in its symptoms, physical examination findings, and additional tests, it is very difficult to distinguish it from thymic adenocarcinoma, which can lead to delayed diagnosis and treatment(6). Case Report: A 58-year-old male presented with shortness of breath. Chest X-ray revealed a mass in the right suprahilar region, which was subsequently confirmed as a mediastinal tumor by contrast-enhanced chest CT scan. The patient underwent open thoracotomy biopsy, and macroscopic examination suggested thymic carcinoma. Histopathological findings revealed atypical cells with bronchoscopic washing and brushing cytology results classified as class II, and Ultrasound guided TTNA only showed debris cells. Diagnostic confirmation took 1.5 years, with immunohistochemistry results showing CK(+), CD45(-), P40(-), Vimentin(-), Napsin A(-), CK7(+), CK20(+), leading to a final diagnosis of enteric-type lung adenocarcinoma with EGFR exon 21 mutation. Conclusion: An accurate diagnosis of enteric-type pulmonary adenocarcinoma requires a multidisciplinary team approach and specific immunohistochemistry (CK7, CK20) to enable precise treatment planning. Keyword: Enteric Tipe Lung Adenocarcinoma, Thymic Adenocarcinoma, Immunohistochemistry